Design and finite element analysis of femoral stem prosthesis using functional graded materials. Issue 11 (15th August 2022) - Ahirwar, Harbhajan; Sahu, Ankit; Gupta, Vijay Kumar; Kumar, Prasoon; Nanda, Himansu Sekhar
Abstract: Conventionally biometals were used for design and development of bioimplants. However, the Young's Modulus (YM) of these bioimplants is higher than that of a natural bone. Asymmetric load transfer from a bone to the bioimplant results in aseptic loosening and stress shielding. Here-in, the use of functionally graded materials (FGM) has been introduced to design the femoral stem prosthesis as a model bioimplant using computational biomechanics. The material properties variations in these FGMs in longitudinal and radial directions are explored to minimize the aseptic loosening and stress-shielding that plays a vital role in defining the performance and longevity of the prosthesis. Three groups of FGM (Ti-HA, SS316L-HA and CoCr alloy-HA) have been explored to design the stem prosthesis and the finite element analysis (FEA) was carried out using computational biomechanics. The stress distribution profile in the designed stem prosthesis demonstrated an increase in the stress values with an increase in the volume fraction exponent. The results corroborated with the stress distribution obtained from the simulation results of a cortico-cancellous bone. The stress distribution in the Ti-HA prosthesis is observed to be more uniform than CoCr-HA and SS316L-HA prosthesis. In addition, the reduced number of stress shielding points were observed for the Ti-HA prosthesis when compared with the CoCr-HA and SS 316 L-HA stem prostheses. Hence, the results suggested that the Ti-HA prosthesis could be considered as a mechanically stable prosthesis and the same could offer safe design for further development of a femoral bioimplant.